Kant's Views on Sex and Marriage and Their Significance for Contemporary Ethics - Fitzerald Kennedy Sitorus (Jurnal Ledalero, 2025)
This paper discusses Kant's thoughts on sex and marriage with the aim of examining their relevance to us today. To that end, the author conducts a sympathetic reading of Kant's writings on sex and discusses Kant's critical and rational assessment of various types of sexual relationships. The results of the study show that the essence of sex in Kant's view is objectification, namely the use of the body as a means to achieve sexual satisfaction. Therefore, intrinsically, every type of sexual relationship is contrary to morality. There is only one form of sexual relationship that does not conflict with the moral law, namely sex conducted within the context of monogamous, lifelong marriage between two people of different sexes. Kant's reflections on sex and marriage are very helpful in enabling us to critically address and construct debates surrounding sex today.